Tert-butyl-diphenylmethylnitroxyl radical formation with the reaction of triphenylbismuth dicrotonate and C-phenyl-N-tert-butylnitrone in benzene - A. V. Gushchin; O. S. Kalistratova; A. I. Maleeva; V. A. Kuropatov; D. N. Yemelyanov (Chimica Techno Acta)
Decomposition of triphenylbismuth dicrotonate in diffused light in bensene in the presence of spin trap of C-phenyl-N-tert-butylnitrone leads to formation of phenyl radicals which are registered as the adduct PhCH(Ph)N(O•)Bu-t.